2018
DOI: 10.1111/acer.13642
|View full text |Cite
|
Sign up to set email alerts
|

Meta‐Analysis of the Association of Alcohol‐Related Social Media Use with Alcohol Consumption and Alcohol‐Related Problems in Adolescents and Young Adults

Abstract: Despite the pervasive use of social media by young adults, there is comparatively little known about whether, and how, engagement in social media influences this group's drinking patterns and risk of alcohol-related problems. We examined the relations between young adults' alcohol-related social media engagement (defined as the posting, liking, commenting, and viewing of alcohol-related social media content) and their drinking behavior and problems. We conducted a systematic review and meta-analysis of studies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
157
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 154 publications
(164 citation statements)
references
References 38 publications
5
157
1
1
Order By: Relevance
“…Given the public nature of these Tweets, it is important to note that they may serve to normalize blacking out as a consequence of drinking (or as the aim of a drinking). There is a substantial body of literature highlighting that individuals (particularly young adults) drink according to their perception of others’ drinking (Borsari and Carey, ) and a number of studies have highlighted that exposure to or engagement with alcohol‐related content on social networking sites may influence behavior (Boyle et al., ; Curtis et al., 2018a,b; Moreno et al., ; Steers et al., ). Thus, exposure to preblackout drinking Tweets may affect an individual's perception of blacking out as a normal consequence of drinking.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Given the public nature of these Tweets, it is important to note that they may serve to normalize blacking out as a consequence of drinking (or as the aim of a drinking). There is a substantial body of literature highlighting that individuals (particularly young adults) drink according to their perception of others’ drinking (Borsari and Carey, ) and a number of studies have highlighted that exposure to or engagement with alcohol‐related content on social networking sites may influence behavior (Boyle et al., ; Curtis et al., 2018a,b; Moreno et al., ; Steers et al., ). Thus, exposure to preblackout drinking Tweets may affect an individual's perception of blacking out as a normal consequence of drinking.…”
Section: Discussionmentioning
confidence: 99%
“…Exposure to and engagement with alcohol‐related social networking content may be linked to alcohol use. Indeed, research suggested that there is a relationship between engaging in alcohol‐related social networking content and alcohol use (Boyle et al., ; Moreno et al., ; Steers et al., ) and a recent metaanalysis suggested that the relationship is moderately strong (Curtis et al., 2018a,b).…”
Section: Alcohol‐related Blackoutsmentioning
confidence: 99%
See 1 more Smart Citation
“…99 Further studies focused on social media and young populations found that alcohol-related social media engagement was correlated with both greater self-reported drinking and alcohol-related problems. 100 This is of extreme importance as young populations are more exposed to alcohol advertising content on social media than adults. 101 The positive use of social media represents an opportunity to target young people.…”
Section: Control Over Alcohol Advertising and Promotionmentioning
confidence: 99%
“…For example, observational analysis of social networking sites has identified problematic prescription opioid use (Carrell et al., ), nonmedical use of psychostimulants (Hanson et al., ), and excessive alcohol consumption (Curtis et al., ). Similarly, a recent meta‐analysis conducted by Curtis and colleagues () reported a significant relationship between posting alcohol‐related content on social networking sites and alcohol consumption behavior and alcohol‐related consequences. While the use and study of social networking sites and digital recovery platforms—such as smartphone applications—remain in its infancy in many ways, preliminary studies suggest that it is useful for observation and identification of substance use behaviors and risk, as well as a potential location for dissemination of health‐focused communication focused on reducing risk and increasing healthy behaviors (Miller and Sønderlund, ).…”
Section: Social Media Language and Alcohol Consumptionmentioning
confidence: 78%